FORENSIC EXAMINATIONS ARE THE MAIN FACTOR IN DETECTING CRIMES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
As we all know, expert opinions are of great importance in determining the circumstances and other circumstances of the commission of crimes. Therefore, a number of documents regulating the field of expertise have been adopted in our legislation, and the procedure for appointing and conducting an expert examination has been clearly defined.